THE VOICE OF WOMEN’S IDENTITY AND THE POETRY OF MAITHILI SHARAN GUPT: A CONTEMPORARY STUDY - Shriprakash (International Journal of Research -GRANTHAALAYAH, 2025)
The question of women’s identity in the Hindi poetic tradition has been a crucial and central aspect of modern literary discourse. However, to assume that women’s consciousness is a product of the modern era would be inappropriate from a literary perspective. In fact, its roots are clearly present in the poetic traditions of Chhayavad and even before that. While in the Bhakti period and the Riti period, women were often seen as a medium of love, beauty, and devotion, moving into the modern era, Chhayavadi poets began to give voice to the inner life of women, their pain, sensitivity, and inner struggle. In this context, the poetry of Maithili Sharan Gupt holds special significance. He is generally considered a national poet, a poet of idealism and Indian moral values, but what remains under-recognized is the depth and sensitivity with which he expressed women’s consciousness and identity. Maithili Sharan Gupt’s poetry can be seen as a bridge between tradition and modernity. He draws on ancient Indian stories and characters, providing them with new ideological contexts. The present study aims to analyze the voice of women’s identity in the specific context of his epic poem "Saket" and his poetic work "Yashodhara." In "Saket," the poet develops a new poetic vision by presenting a traditional, male-centric narrative like the Ramayana from Urmila’s perspective. Urmila is no longer merely Lakshmana’s wife or a woman of sacrifice; rather, she emerges as a woman fully aware of her rights, emotions, and self-respect. Her silence is not merely a symbol of tolerance, but rather becomes the voice of deep self-control and inner resistance, through which she exposes the neglect and suffering of women’s lives. Similarly, in "Yashodhara," the character of Yashodhara offers another powerful expression of female identity. Yashodhara’s silent lamentation over her husband Siddhartha’s decision to renounce the world, but rather her thoughtful questioning, is a testament to feminine consciousness. She accepts this decision not merely as a spiritual achievement but examines it against the touchstone of familial, social, and human obligations. Yashodhara emerges as a thoughtful woman, seeking a balance between love, duty, and sacrifice, who refuses to allow her existence to be subsumed by the shadow of a man. Maithili Sharan Gupt’s portrayal of women is neither limited to compassion and tolerance nor inclined toward radical rebellion. His women are rooted in Indian cultural values, yet they possess self-awareness and the courage to understand and question their own lives. Thus, Maithili Sharan Gupt’s poetry, while establishing women’s identity on a moral and cultural level, also provides a strong ideological foundation for modern feminist discourse. The voices of women’s identity, as expressed in "Saket" and "Yashodhara," provide Hindi poetry with a sensitive, balanced, and thought-provoking perspective that remains relevant and valuable even today.